Chemical composition and biological activities of essential oils of Foeniculum vulgare Mill. and Daucus carota L. growing wild in Turkey - DOĞAN, AHMET; ŞEN, ALİ (MARMARA UNIV, 2021)
The chemical composition of essential oils of aerial parts of Daucus carota (DEO) and Foeniculum vulgare (FEO) was specified by GC/MS. Antidiabetic, anti-inflammatory, antioxidant, and antibacterial activities of oils were tested by alpha-glucosidase inhibitory, 5-lipoxygenase inhibitory, DPPH/ ABTS radical scavenging, and broth microdilution methods, respectively. Thirty components were identified in DEO (87.7%). Carotol (27.7%), elemicin (18.1%), and limonene (16.0%) were determined as the main compounds in DEO. Seventeen constituents were identified in FEO (100.0%). Estragole (34.0%), limonene (27.1%), and alpha-pinene (19.5%) were found as major components in FEO. Both oils displayed weak antibacterial activity against Gram-negative bacteria. However, the oils were not effective on Grampositive bacteria. DEO with IC50 values of 1359 and 1579 mu g/mL and FEO with IC50 values of 3106 and 1654 mu g/mL showed weak antioxidant activities against DPPH and ABTS radicals, respectively. DEO and FEO exhibited good antilipoxygenase activities with IC50 values of 87.24 and 58.35 mu g/mL, respectively. DEO presented significantly alpha-glucosidase inhibitory activity with an IC50 value of 44.78 mu g/mL while FEO displayed poor activity with an IC50 value of 1%7 mu g/mL. This study is the first report on the 5-lipoxygenase and alpha-glucosidase inhibitory activities of aerial parts of DEO as well as on the alpha-glucosidase inhibitory activity of aerial parts of FEO. These results indicated that DEO, which has a good antidiabetic and anti-inflammatory activity, is rich in oxygenated sesquiterpene and monoterpene. Also, it showed that FEO, which has a significant anti-inflammatory activity, is rich in monoterpene and phenylpropanoid.
Keywords: Daucus carota; Foeniculum vulgare; essential oils; biological activity; ANTIMICROBIAL ACTIVITIES; ANTIOXIDANT ACTIVITY; CULTIVATED CARROTS; SEEDS; EXTRACTS; VARIABILITY; COMPONENTS; CHEMOTYPE; APIACEAE; FRUITS